Mokhtar - Ridhwan Ismail (Nanyang Technological University, 2022)
Mokhtar regains his consciousness in the forest. He attempts to get up but is unable to do so. He hauls himself up to the nearest body for supplies but does not find much off of his dead comrade except for a rifle. Movement in the undergrowth catches his eye and upon realising it was an enemy soldier. (Hiroo), Mokhtar attempts to attack him. Mokhtar fails to injure Hiroo and after realising that he is a medic, he demands that Hiroo hands over his supplies but the medic has other ideas and attempts to kill him instead. A short tussle ensues with the medic being knocked out cold and Mokhtar fatigued. When they both regain consciousness, they realise they would need to rely on each other to survive. As they interact with each other, they begin to gain each other’s trust and eventually, Hiroo patches up Mokhtar's leg wound.